An Integrated Semasiological and Onomasiological Presentation of Semantic Information in General Monolingual Dictionaries as Proposed in H.E. Wiegand’s Semantics and Lexicography - Louw, Phillip (Lexikos, 2000)
Abstract: Herbert Ernst Wiegand is a very important figure in international metalexicography. A large part of his research has up to now been unavailable to the majority of the English-speaking world, because it has mainly been published in German. A new book Semantics and Lexicography seeks to break through this obscurity by providing English translations of a selection of articles spanning thirty years (from 1976 to 1996), which trace the development of Wiegand’s views on semantic information. This book offers a valuable insight into the theoretical and corresponding terminological development that has already had such a remarkable impact on the "practical science" metalexicography. This article focuses on Wiegand’s theories on the integration of the semasiological and onomasiological presentation of semantic information in the microstructures of general monolingual dictionaries. The theories are explicated and illustrated by examples from two Afrikaans general monolingual dictionaries and evaluated in order to establish their relevance. The conclusion is reached that the semasiological presentation of meaning is most appropriately located in the item giving the meaning paraphrase, which should form part of the semantic comment in an integrated microstructure. In the semantic comment, this item must be followed by dearly distinguished items giving onomasiological information, especially about synonymy. Keywords: DEFINITION, FRAME, HYPONYM, ITEM GIVING THE MEANING PARAPHRASE, LEXICAL PARAPHRASE, LEXICOGRAPHIC PARAPHRASE, METALEXICOGRAPHY, NEAR-SYNONYM, OBJECT-CONSTITUTING KNOWLEDGE; ONOMASIOLOGICAL, SEMANTIC RELATION, SEMASIOLOGICAL, SYNONYM, SYNONYM DEFINITION. Opsomming: In Ge’integreerde semasiologiese en onomasiologiese aanbod .van semantiese inligting in algemeen eentalige woordeboeke soos voorgestelin H.E. Wiegand se Semantics and Lexicography. Herbert Ernst Wiegand is ’n baiebelangrike figuur in die intemasionale metaleksikografie. ’n Groot deel van sy navorsing was tot nou toe ontoeganklik vir die meerderheid mense in die Engelssprekende wereld. ’n Nuwe boeksemantics and uxicography poog om sy werk beter bekend te stel deur Engelse vertalings te verskafvan ’n seleksie van sy artikels wat strek Qor dertig jaar (van 1976 tot 1996) en die ontwikkeling vansy sienings oor semantiese inIigting uit te Ie. Hierdie boek bied derhalwe ’n waardevolle insig indie teoretiese en gepaardgaande terminologiese ontwikkeling wat al so ’n merkwaardige invloedop die "praktiese wetenskap" metaleksikografie gehad he!.Hierdie artikel fokus op Wiegand se teoriee van die integrasie van ’n semasiolo’giese en onomasiologieseaanbod van semantiese inIigting in algemeen eentalige woordeboeke. Die teorie!!word verduidelik en geillustreer deur mid del van voorbeelde uit twee Afrikaanse algemeen eentaligverklarende woordeboeke en geevalueer om hulle relevansie vas te stel. Daar word tot die gevolgtrekkiilg gekom dat die semasiologiese aanbod van semantieseinligting ten beste inpas in die item wat die betekenisparafrase aanbied, wat deel behoort uit temaak van die semantiese kommentaar in ’n gemtegreerde mikrostruktuur. Hierdie item moet in diesemantiese kommentaar gevolg word deur deeglik afgebakende items wat onomasiologiese informasie, veral oor sinonimie, oordra. Sleutelwoorde: DEFINISIE, HIPONIEM, ITEM WAT DIE BETEKENISPARAFRASEAANBIED, LEKSIKALE PARA FRASE, LEKSIKOGRAFIESE PARA FRASE, METALEKSIKOGRAFIE, NABYSINONIEM, OBJEKBEPALENDE KENNIS, ONOMASlOLOGIES, RAAM, SEMANTIESE VERHOUDING, SEMASIOLOGIES, SINONIEM, SINONIEMDEFINISIE.